Estudo sobre a redução aluminotérmica de Ta2O5 e TiO2 usando descarga de cátodo oco - Brito, Roseane Aparecida de (2011)
In this study it was used two metallic oxides, Ta2O5 and TiO2, in order to obtain metallic powders of Ta and Ti through aluminothermic reduction ignited by plasma. Ta2O5 and TiO2 powders were mixed with Al in a planetary mill, using different milling times. A thermal analysis study (DTA and TG) was carried out, in order to know the temperature to react both the mixtures. Then, these mixtures were submitted to a hollow cathode discharge, where they were reacted using aluminothermic reduction ignited by plasma. The product obtained was characterized by XRD and SEM, where it was proven the possibility of producing these metallic particles, different from the conventional process, where metallic ingots are obtained. It was verified that the aluminothermic reduction ignited by plasma is able to produce metallic powders of Ta and Ti, and a higher efficiency was observed to the process with Ta2O5-Al mixtures. Among different microstructural aspects observed, it can be noted the presence of metallic nanoparticles trapped into an Al2O3 matrix, besides acicular structures (titanium) and dendritic structures (tantalum), which are a product characteristic from a fast cooling